Controllability of runoff attributes on a saline soil treated by cyanobacteria inoculant - GHAREMAHMUDLI, SUDABEH; SADEGHI, SEYED HAMIDREZA (Journal of Soil and Water Conservation, 2025)
Soil erosion is a significant challenge to maintain and improve the degradation of productive soils in saline areas worldwide. Considering the harmful effects of soil erosion extra runoff in saline areas, it explains the necessity of using effective and permanent methods to control soil and water loss. Nowadays, soil microorganisms are used as soil inoculants to promote biotechnological methods for soil and water conservation. However, the effect of microorganisms’ inoculation on runoff attributes is yet to be studied. Therefore, the present study strived to determine the role of inoculation of native soil cyanobacteria of the studied area in controlling the surface runoff attributes of saline soil in the laboratory. In this regard, the studied soil was prepared from the saline lands of the Incheh Borun Region, Golestan Province, Iran, and transferred to small erosion plots (0.5 × 0.5 m) in the Rain and Soil Erosion Simulation Laboratory of Tarbit Madras University. Then, the most suitable cyanobacteria effective in soil and water loss inhibition and available in the soil microorganism bank of the region, after preparation and identification, were selected, purified, and propagated. Comparison of control and inoculated cyanobacteria treatments on saline soil in simulated rain conditions lasting 30 min and intensity of about 70 mm h-1 was made after 60 days of inoculation with 10% slope with three replications. The research findings showed that, the inoculation treatments compared to the control treatment significantly (p